Effect of Performance-Based Budgeting and Financial Reporting Systems on the Performance Accountability of Bekasi Regency Government Agencies - Laura Wahdatul; Iskandar Muda; Keulana Erwin (Budapest International Research and Critics University, 2021)
This study aims to determine and analyze the effect of performance-based budgeting and financial reporting systems on the performance accountability of Bekasi Regency Government Agencies. This study uses a quantitative survey method by distributing questionnaires to the finance department in each regional unit of Bekasi Regency. The population in this study were 38 regional work units of Government Agency Performance Units (SKPD) in Bekasi Regency. Determination of the sample with this study using random sampling method so that a sample of 125 people was obtained where 3 to 4 people were in the finance department in each regional unit in Bekasi Regency. The data were analyzed using descriptive statistical analysis and partial least squares analysis (SEM-PLS) with the smart PLS 3.0 software program. The results of this study indicate that performance-based budgeting has a significant effect on the performance accountability of Bekasi Regency Government Agencies. Financial reporting systems has a significant effect on the performance accountability of Bekasi Regency Government Agencies.